Texture Related Inhomogeneous Deformation and Fracture Localization in Friction-Stir-Welded Magnesium Alloys: A Review - Ren, Weijie; Xin, Renlong; Tan, Chuan; Liu, Dejia (Frontiers in Materials, 2020)
Friction stir welding (FSW) is a solid-state joining technique, which can avoid surface distortion and grain coarsening, and is very suitable for the joining of magnesium (Mg) alloys. However, a strong and complicated deformation texture was usually formed in the stir zone (SZ) of Mg welds. This has significant effect on the joint strength and fracture behaviors of FSW Mg joints. In this review, microstructure and texture evolutions in weld zone (WD) are analyzed based on the electron backscatter diffraction (EBSD) data. Schmid factor (SF) changes for slip and extension twinning were observed and discussed. The localized plastic deformation and fracture mechanism of Mg welds are analyzed. In addition, some methods for improving the joint strength of FSW Mg welds are reviewed. Finally, the research direction of FSW Mg alloys in the future is prospected.